Map Learning with a 3D Printed Interactive Small-Scale Model: Improvement of Space and Text Memorization in Visually Impaired Students - Giraud, Stéphanie; Brock, Anke M.; Macé, Marc J.-M.; Jouffrais, Christophe (Frontiers in Psychology, 2017)
Special education teachers for visually impaired students rely on tools such as raised-line maps to teach spatial knowledge. These tools do not fully and adequately meet the needs of the teachers because they are long to produce, expensive, and not versatile enough to provide rapid updating of the content. For instance, the same raised-line map can barely be used during different lessons. In addition, those maps do not provide any interactivity, which reduces students’ autonomy. With the emergence of 3D printing and low-cost microcontrollers, it is now easy to design affordable interactive small-scale models which are adapted to the needs of special education teachers. However, no study has previously been conducted to evaluate non-visual learning using interactive small-scale models. In collaboration with a specialized teacher, we designed a small-scale model and a raised-line map representing the evolution of the geography and history of a fictitious kingdom. The two conditions were compared in a study with 24 visually impaired students regarding the memorization of the spatial layout and historical contents. The study showed that the interactive small-scale model improved both space and text memorization as compared to the raised-line map with braille legend. In conclusion, we argue that affordable home-made interactive small scale models can improve learning for visually impaired students. Interestingly, they are adaptable to any teaching situation including students with specific needs.